การประเมินการใช้หลักสูตรประกาศนียบัตรวิชาชีพชั้นสูง พุทธศักราช 2557 ประเภทวิชาบริหารธุรกิจ สาขาวิชาคอมพิวเตอร์ธุรกิจ ของนักศึกษาวิทยาลัยเทคโนโลยีซีเทคแปซิฟิค จังหวัดพะเยา - ไชยพันธ์พงษ์, สุรเจต; เจนเขว้า, เสวียน (Academic Journal Phranakhon Rajabhat University, 2017)
The purpose of this research was to evaluate curriculum implementation of Diploma in Business Administration (2014) majoring in Computer Business of CTECH Pacific College of Technology Student. Population were 121 last-year Diploma in Business Administration student majoring in Computer Business. Instrument used for collecting data was a questionnaire with three parts; Part one cover general data with Checklist, Part two was the 5-item rating scale questionnaire concerning opinion in 4 aspects of curriculum implementation evaluation by CIPP Model of Stufflebeam, and part three was an open-end questionnaire for general opinion. The statistical devices used were percentage, arithmetic mean (µ) and standard deviation (σ) Result revealed that: 1. Overall, opinion of curriculum implementation evaluation by CIPP Model of Stufflebeam were in the high level (µ = 3.76) 2. Considering by aspect, Student’s opinion were in the high level of each aspect with Context aspect (µ = 3.82) Process aspect (µ = 3.77) Input aspect (µ = 3.74) and Product aspect (µ = 3.71) respectively.